IMPLEMENTASI PROBLEM BASED LEARNING UNTUK MENINGKATKANPEMAHAMAN MATERI SHALAT DI SD NEGERI 050784 LIMAU MUNGKUR - Ade Wiki (Journal of Community Devation, 2024)
The students' understanding of the prayer material at SD Negeri 050784 Limau Mungkur has not been optimal, influenced by several factors such as students' interest and motivation in learning as well as the teaching methods used by the teacher. One effort to improve students' comprehension is through the implementation of the Problem Based Learning (PBL) approach, which encourages students to actively participate in the learning process by solving problems relevant to their daily lives. This classroom action research aims to determine whether the application of PBL can enhance the understanding of prayer material among fourth-grade students. The research subjects were fourth-grade students at SD Negeri 050784 Limau Mungkur during the second semester of the 2023/2024 academic year. The results showed that by the end of the second cycle, students' learning mastery reached 93%, where 27 out of 29 students scored ≥ 75 (the Minimum Competency Standard). Meanwhile, 7% of students did not meet the standard with scores ≤ 75. This result met the research's success criteria, which required ≥ 80% of students to achieve scores ≥ the Minimum Competency Standard. Both teacher and student activities also showed positive results, with success rates reaching 93% for teacher activities and 94% for student activities. Both activities were categorized as very good. Thus, it can be concluded that the implementation of the Problem Based Learning approach can improve the understanding of prayer material among fourth-grade students at SD Negeri 050784 Limau Mungkur.